2003
DOI: 10.1002/pola.10793
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of conjugated copolymers containing phenothiazinylene vinylene moieties and their electrooptic properties

Abstract: Four different types of conjugated copolymers, consisting of alternating structures of phenothiazinylene vinylene and phenylene vinylene derivatives such as phenylene vinylene, 1,1′‐biphenyl‐4,4′‐ylene vinylene, 2‐methoxy‐5‐(2‐ethylhexyloxy)‐1,4‐phenylene vinylene, and 9,10‐anthrylene vinylene, were prepared by Horner–Emmons condensation between appropriate diphosphonates and dialdehydes. Single‐layer and double‐layer light‐emitting diodes were fabricated with the synthesized conjugated polymers, and their ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…N-(2-ethylhexyl)-3,6-diformylphenothiazine (DFPZ) [12] Phosphoryl chloride (122.7 g, 0.8 mol) was added dropwise over a period of 30 min to a mixture of N-(2-ethylhexyl)phenothiazine (EHPZ) (12.36 g, 0.04 mol) and N,N-dimethylformamide (DMF) (58.5 g, 0.8 mol) in 1,2-dichloroethane (15 ml) in an ice bath. The solution was refluxed for 72 h. DFPZ was obtained as liquid in 69% yield.…”
Section: Monomer Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…N-(2-ethylhexyl)-3,6-diformylphenothiazine (DFPZ) [12] Phosphoryl chloride (122.7 g, 0.8 mol) was added dropwise over a period of 30 min to a mixture of N-(2-ethylhexyl)phenothiazine (EHPZ) (12.36 g, 0.04 mol) and N,N-dimethylformamide (DMF) (58.5 g, 0.8 mol) in 1,2-dichloroethane (15 ml) in an ice bath. The solution was refluxed for 72 h. DFPZ was obtained as liquid in 69% yield.…”
Section: Monomer Synthesismentioning
confidence: 99%
“…1 N-(2-ethylhexyl)-3,6-diformylcarbazole (DFCZ) [13] Phosphoryl chloride (122.7 g, 0.8 mol) was added dropwise over a period of 30 min to a mixture of N-(2-ethylhexyl)carbazole (EHCZ) (11.18 g, 0.04 mol) and DMF (58.5 g, 0. 1,4-Bis(diethoxyphosphinylmethyl)benzene (PHBZ) [12] PHBZ was synthesized by reacting a,a 0 -dichloro-p-xylene (33 g, 0.2 mol) with triethylphosphite (33 g, 0.2 mol) at 120 C for 12 hr. The unreacted triethylphosphite was removed under reduced pressure.…”
Section: Monomer Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Phenothiazine is a well-known heterocyclic compound with electron-rich nitrogen and sulfur heteroatom. Conjugated polymers and copolymers based on phenothiazine have been investigated [1][2][3][4][5][6][7]. It has been demonstrated that phenothiazine unit is an excellent p-type building block for lowering ionic potential of conjugated polymers due to its readily injection and transport of hole and the non-planarity of phenothiazine impedes p-stacking aggregation and intermolecular excimer formation which may lead to the poor quantum efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Known as fluorescent dyes, phenothiazine monomer can be easily tailored by connecting flexible groups to the N‐position to improve solubility or varying the aromatic structure with functional groups for further polymerization. Conjugated copolymers based on phenothiazine have been investigated in recent years 3–12. It has been demonstrated that phenothiazine unit is an excellent p ‐type building block for lowering ionic potential of conjugated polymers due to its readily injection and transport of hole.…”
Section: Introductionmentioning
confidence: 99%